Principles of Electrical Safety - Sutherland, Peter E. (Hoboken : Wiley, 2014)
Principles of Electrical Safety discusses current issues in electrical safety, which are accompanied by series' of practical applications that can be used by practicing professionals, graduate students, and researchers. Provides extensive introductions to important topics in electrical safety. Comprehensive overview of inductance, resistance, and capacitance as applied to the human body. Serves as a preparatory guide for today's practicing engineers.
9.2 Three-Phase Multigrounded Neutral Distribution Line9.3 Secondary Systems: 120/240V Single Phase; 9.4 Remediation of Stray-Current Problems; 9.5 Grounding and Overvoltages in Distribution Systems; 9.6 High-Resistance Grounding of Distribution Systems; Chapter 10: Arc Flash Hazard Analysis; 10.1 Introduction to Arc Flash Hazards; 10.2 Factors Affecting the Severity of Arc Flash Hazards; 10.3 Example Arc Flash Calculations; 10.4 Remediation of Arc Flash Hazards; 10.5 Coordination of Low-Voltage Breaker Instantaneous Trips for Arc Flash Hazard Reduction.
10.6 Low-Voltage Transformer Secondary Arc Flash Protection using Fuses.
Print version record.
Keywords: Electrical engineering -- Safety measures; Electricity -- Safety measures; Electric apparatus and appliances -- Safety measures; Electric apparatus and appliances -- Safety measures; Electrical engineering -- Safety measures; Electricity -- Safety measures; Electric apparatus and appliances -- Safety measures; Electrical engineering -- Safety measures; Electricity -- Safety measures; Electronic books